Antibody immunoprophylaxis and immunotherapy for influenza virus infection: Utilization of monoclonal or polyclonal antibodies? - Cassandra M. Berry (Taylor & Francis Group, 2018)
Control programs for emerging influenza are in urgent need of novel therapeutic strategies to mitigate potentially devastating threats from pathogenic strains with pandemic potential. Current vaccines and antivirals have inherent limitations in efficacy, especially with rapid evolutionary changes of influenza viruses. Antibody-based antiviral protection harnesses the natural power of the immune system. Antibodies present prophylactic and therapeutic intervention options for prevention and control of influenza, especially for at-risk populations. Specific monoclonal antibodies are well defined in purity and initial efficacy but polyclonal antibodies are easier to scale-up and cost-effective with long-term efficacy, using batches with broadly neutralizing properties against influenza variants. This review presents the pros and cons of monoclonal versus polyclonal antibody therapy for influenza.